2009
DOI: 10.1097/mpa.0b013e3181a86b74
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Inhibits the Development of Acute Pancreatitis and Nuclear Factor κB Activation in Pancreas and Liver

Abstract: Ghrelin inhibits the development of acute pancreatitis induced by sodium taurocholate. It exerts the therapeutic effects through inhibiting NF-kappaB expression, thereby blocks the inflammatory signal transduction pathway and reduces the release of inflammatory media and cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 37 publications
2
39
1
Order By: Relevance
“…The cck mRNA levels decrease by fasting in different fish species (Murashita et al, 2006;Feng et al, 2012;Ji et al, 2015), conversely ghrelin increase mRNA levels by fasting (Amole & Unniappan, 2009;Zhou & Xue, 2009;Tian et al, 2015;Volkoff, 2015;Blanco et al, 2016). These gene expression modulations were not observed in our results.…”
Section: Discussioncontrasting
confidence: 50%
“…The cck mRNA levels decrease by fasting in different fish species (Murashita et al, 2006;Feng et al, 2012;Ji et al, 2015), conversely ghrelin increase mRNA levels by fasting (Amole & Unniappan, 2009;Zhou & Xue, 2009;Tian et al, 2015;Volkoff, 2015;Blanco et al, 2016). These gene expression modulations were not observed in our results.…”
Section: Discussioncontrasting
confidence: 50%
“…Ghrelin is a newly discovered peptide with various functions, including regulating energy metabolism, promoting cell proliferation [19]. Recent studies have demonstrated that ghrelin attenuates inflammatory injury [13,15,16,20,21]. Okamatsu et al have shown that serum ghrelin level is significantly elevated with liver function index in overweight children [22].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ghrelin on pro-inflammatory cytokines induction and release has been related, in several studies, to a suppression of the expression and/or activity of the transcription factor NF-jB (Barazzoni et al 2014;Hou et al 2009;Konturek et al 2006;Li et al 2004;Liu et al 2010;Peng et al 2012;Slomiany and Slomiany 2013;Wang et al 2012;Waseem et al 2008;Wu et al 2005;Yuan et al 2009;Zhou and Xue 2009). However, it has been proposed that in some circumstances and with some cell types, ghrelin may act as a pro-inflammatory peptide inducing, rather than reducing, NF-jB expression and proinflammatory IL-8 secretion (Kwan et al 2010;Rezaeian et al 2012;Sung et al 2011;Zhao et al 2006).…”
Section: Ghrelin and Ghs-r1a Mrna Expression And Distribution In The mentioning
confidence: 99%